Meningkatkan Hasil Belajar Siswa melalui Model Pembelajaran Koopertif dalam Pembelajaran IPA di Kelas 5 SD Negeri Kramat 1 Kecamatan Dempet - Niam, Saiful (Jurnal Kualita Pendidikan, 2024)
Science learning in the classroom still positions students as listeners to the teacher's lectures, as a result learning is boring, and students are less active. The impact is that student learning outcomes are less than optimal. The purpose of this study was to describe learning activities, learning management and student learning outcomes during the application of the cooperative learning model in 5th grade science learning at SD Negeri Kramat 1. This study was designed with classroom action research. The results showed that the most prominent student learning activities were observing, experimenting, or working, which always increased in each cycle. Learning management has been able to master students in learning. Student learning outcomes in science learning through the application of cooperative learning models have increased a lot. Taking into account the results of the study, the researchers suggest that teachers should not place students as listeners to the teacher's lectures, but treat them as actors of learning, teachers need to choose, design, and apply appropriate learning models to improve student learning outcomes.